ALLIES: THE ACLU AND THE TOBACCO INDUSTRY (Tufts Archival Research Center, 2007)
Report sponsored by the Coalition on Smoking or Health, Ralph Nader, and others analyzes the American Civil Liberties Union’s (ACLU) relationship with the tobacco industry. Emphasizes conflict of interest between the American Civil Liberties Union accepting donations from Philip Morris and lobbying for tobacco industry interests, while not disclosing to members that it receives money from the tobacco industry. States that in author’s opinion, this is unacceptable because the use of tobacco leads to millions of preventable death. Includes statistics about effects from secondhand smoke on children and other non smokers.